Anticancer Targets in the Glycolytic Metabolism of Tumors: A Comprehensive Review - Porporato, Paolo E.; Dadhich, Rajesh K.; Dhup, Suveera; Copetti, Tamara; Sonveaux, Pierre (Frontiers in Pharmacology, 2011)
Cancer is a metabolic disease and the solution of two metabolic equations: to produce energy with limited resources and to fulfill the biosynthetic needs of proliferating cells. Both equations are solved when glycolysis is uncoupled from oxidative phosphorylation in the tricarboxylic acid cycle, a process known as the glycolytic switch. This review addresses in a comprehensive manner the main molecular events accounting for high-rate glycolysis in cancer. It starts from modulation of the Pasteur Effect allowing short-term adaptation to hypoxia, highlights the key role exerted by the hypoxia-inducible transcription factor HIF-1 in long-term adaptation to hypoxia, and summarizes the current knowledge concerning the necessary involvement of aerobic glycolysis (the Warburg Effect) in cancer cell proliferation. Based on the many observations positing glycolysis as a central player in malignancy, the most advanced anticancer treatments targeting tumor glycolysis are briefly reviewed.